The influence of freeplay on the whirl flutter and nonlinear characteristics of rotor-nacelle systems - Quintana, A.; Saunders, B. E.; Vasconcellos, R. [UNESP]; Abdelkefi, A. (Springer Nature, 2023)
Rotor-nacelle systems are susceptible to aeroelastic instabilities, such as whirl flutter, which is affected by structural and/or aerodynamic nonlinearities. This phenomenon can lead to structural fatigue and possible failure in propeller-driven aerodynamic systems. A nonlinear reduced-order model using quasi-steady aerodynamics for a rotor-nacelle system is considered to study the effects of whirl flutter and structural freeplay nonlinearity on the performance of rotor-nacelle systems. The results of the freeplay with various gap sizes and stiffnesses are explored in the dynamical responses of these rotor-nacelle systems. A particular focus is paid to the interaction between the freeplay nonlinearity and inherent structural nonlinearities in the system's degrees of freedom. First, several polynomial nonlinearities considering a two-degree-of-freedom rotor-nacelle model are tested to research possible structural nonlinear effects with freeplay. Results show that the gap size affects the bifurcation diagrams resulting in a variation in the oscillation amplitudes with period-adding behaviors. The characterization of one specific case is considered, deeply investigated, and discussed. For particular transition points, characterizations are analyzed using the time histories, power spectra, phase portraits, Poincaré maps, and basin of attraction. Lastly, case studies are performed to determine the impacts of freeplay, structural nonlinearities, and particular parameters on the system’s dynamics (i.e. blade length, chord length, rotor moment of inertia, nacelle moment of inertia, and number of blades). Based on the result found, the six-blade propeller case is selected and studied as a case of interest, where complex and period-adding behavior are uncovered.
Keywords: Aeroelastic instability; Bifurcation analysis; Freeplay; Nonlinear dynamics; Rotor-nacelle systems; Whirl Flutter